(untitled) (Journal of Atomic and Molecular Sciences, 2018)
In present work, we investigated the surface-enhanced raman scattering (SERS) of 4,4’-bipyridine on Graphene surface with a quasi-analytical approach based on density functional perturbation theory (DFPT). Three different configurations were considered to simulate the adsorption structures on the Graphene surface. The interaction between 4,4’-bipyridine molecule and Graphene surface depends on the adsorption structure, which also results in the distinct spectroscopy. The relationship between the configurations and SERS spectroscopy were interpreted. We also performed the experimental SERS spectroscopy of 4,4’-bipyridine molecule on Graphene. Comparing with the experimental SERS spectroscopy, the landscape of 4,4’-bipyridine on Graphene has been revealed.